Analytics of IoT Data for Smart Cities on the Cloud - Gar, Umang (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
A smart city is one that has some of the most advanced and useful IoT programmes in use. In the last several years, the concept of smart city integration has been more important in academic, healthcare, and industrially focused areas. Cloud computing and the Internet of Things (IoT) are two well-known information and communication technology (ICT) standards that are likely to shape the next era of processing. The proposal depicts an appealing platform for various forms of technology-enabled government discontent. It provides a vision of the city in which specialised organisations use specialised data to collaborate with residents and shape a thriving urban culture by designing infrastructure that may boost individual happiness. Because of its flexibility to adapt to new environments, the Internet of Things (IoT) will be able to seamlessly combine a vast number of programmes at varying levels of development. This will initiate the release of a small, authorised data collection that may be used to effect change across a variety of modernised institutions. IoT frameworks in urban areas are suggested to make smart cities a reality. The topic at hand is the evolving systems of reciprocal assistance that the city's many institutions and families rely on. This article presents and discusses the fundamental configurations and technological standards that must be embraced in a city in order to make it smarter. As a result, the standard of living and general welfare of the populace will improve thanks to this strategy.